Circular RNA profiling identifies circADAMTS13 as a miR‐484 sponge which suppresses cell proliferation in hepatocellular carcinoma. Issue 2 (9th January 2019) - Qiu, Liman; Huang, Yanbing; Li, Zhenli; Dong, Xiuqing; Chen, Geng; Xu, Haipo; Zeng, Yongyi; Cai, Zhixiong; Liu, Xiaolong; Liu, Jingfeng
Abstract : Circular RNA (circRNA) can participate in various biological processes, including tumorigenesis, through their microRNA response elements. Alterations in circRNA profiles during hepatocellular carcinoma (HCC) progression and their clinical significance remain unclear. Here, we present extensive analysis of circRNA profiles in tumor and matched peritumor tissues collected from 10 HCC patients, conducted to identify circRNA related to HCC progression. A total of 42 dysregulated circRNA (38 down‐regulated and 4 up‐regulated) were identified in HCC tumor tissues compared with matched peritumor tissues, revealing the heterogeneity of circRNA profiles in HCC. CircADAMTS13, derived from Exon 13–14 of the ADAMTS13 gene, was significantly downregulated in HCC tumor tissues. Furthermore, clinicopathological analysis revealed that up‐regulation of circADAMTS13 was negatively associated with tumor size but positively associated with prognosis. In addition, overexpression of circADAMTS13 could markedly inhibit HCC cell proliferation in vitro . Bioinformatic analysis and luciferase reporter assays further revealed that circADAMTS13 directly interacts with microRNA (miR)‐484. Rescue experiments showed that miR‐484 mimics can reverse the tumor‐suppressing roles of circADAMTS13 in HCC. Therefore, our results demonstrated that circADAMTS13 can serve as a tumor suppressor during HCC progression via the functional pathway of sponging miR‐484. Abstract : Here, we investigated tumor heterogeneity of circRNA profiles during hepatocellular carcinoma (HCC) progression, thereby identifying circular RNAs related to tumorigenesis and development. We identified a novel HCC‐related circRNA molecule, circADAMTS13, which has a functional role in inhibiting tumor proliferation through sponging oncogenic miR‐484, and is positively associated with HCC prognosis.